Assessment of students performances in biology: Implication for measurements and evaluation of learning - Ado Abdu Bichi; Rahinatu Hassan Ibrahim; Fatima B Ibrahim (Intelektual Pustaka Media Utama, 2019)
Scienceeducation is believed to be a vital tool for individual and societal development at large. The persistent low levels of students’ achievement in sciences at the various public examinations in Nigeria have continued to draw the attention of major stakeholders in education. This study examined academic achievement of Senior Secondary School students in biology and gender difference in students’ achievement was examined. Ex-post facto design of descriptive research was adopted for the study. A proforma was used to collect data from a sample of two hundred (200) students, selected using stratified random sampling procedure from the Science secondary schools in Kano state Nigeria. The data collected were the students’ performances in biology achievement tests. The data were analysed using descriptive statistics and independent-sample t-test. Overall results showed that the test internal consistency reliability is low and unsatisfactory; the students performed below average (M=47.02, SD=16.493 (47%). Similarly, gender difference exists in biology performance with another significant difference between performance of urban and rural school students. The study concludes that, biology test used in Kano state qualifying examinations to assess students potential ability in biology is not a reliable measurement tool and that, academic performance of students in biology is unsatisfactory and evidence of differential performance between gender and schools locations. The implication for measurements and evaluation of learning as well as recommendations has been discussed.